Secondary battery and method for preparing the same
By covering the surface of the silicon-based anode material of the secondary battery with titanium nitride and MOFs layers, the problems of low conductivity and serious volume expansion of the silicon-based material are solved, and the conductivity and cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411514649.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-10-28
AI Technical Summary
When the negative electrode of existing secondary batteries is made of silicon-based materials, its conductivity is low and its volume expansion is severe, resulting in poor conductivity and cycling performance of the battery.
The titanium nitride layer is coated on the surface of the silicon-based core, and the MOFs material is coated on the surface of the titanium nitride layer to form a composite structure of the silicon-based core @titanium nitride @MOFs to improve the conductivity and stability of the silicon-based negative electrode material.
It significantly enhances the conductivity, energy density and cycling performance of the secondary battery, avoids direct contact between silicon-based materials and electrolyte, and improves the stability and cycling performance of the material.
Smart Images

Figure CN119029338B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a secondary battery and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy market, such as the rapid development of new energy vehicles, based on the high energy density and fast charging performance requirements of secondary batteries such as lithium-ion batteries, lithium battery negative electrode materials are accelerating their penetration into silicon-based negative electrodes. Among lithium-ion battery materials, negative electrode materials are an important component and can have a significant impact on the performance of the overall battery. At present, negative electrode materials are mainly divided into two categories, one is carbon materials for commercial applications, such as natural graphite, soft carbon, etc., and the other is non-carbon negative electrode materials that are in the research and development stage but have good market prospects, such as silicon-based materials, alloy materials, tin gold materials, etc. The theoretical specific capacity of graphite negative electrode is 372mAh / g, and the theoretical specific capacity of silicon negative electrode can reach 4200mAh / g, which is about 10 times that of graphite negative electrode. In scenarios with higher energy density requirements, silicon-based materials are the first choice for negative electrode materials.
[0003] However, because silicon is a semiconductor, its conductivity is poor, and during the embedding process, its volume will expand several times, with the highest expansion rate reaching 370%. This will cause the active silicon to pulverize and fall off, making it difficult to fully contact with electrons, which will lead to a rapid reduction in capacity and poor cycle performance. Therefore, improving the conductivity of silicon, inhibiting the volume expansion of silicon, and enhancing its cycle performance are the key points that need to be urgently addressed in the application of silicon negative electrodes in lithium batteries. Summary of the invention
[0004] The main purpose of the present invention is to provide a secondary battery and a preparation method thereof, so as to solve the problem in the prior art that when the negative electrode of the secondary battery uses silicon-based materials, its conductivity is low and its volume expands seriously, resulting in poor conductivity and cycle performance of the battery.
[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, there is provided a secondary battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, the negative electrode comprising a silicon-based negative electrode material, the silicon-based negative electrode material comprising: a silicon-based core, a titanium nitride layer coated on the surface of the silicon-based core, and a MOFs coating layer coated on the surface of the titanium nitride layer; the material of the silicon-based core comprises one or more of silicon monoxide, silicon dioxide, silicon and silicon-carbon materials; the material of the MOFs coating layer comprises one or more of ZIF-8, ZIF-67 and UIO-66.
[0006] Furthermore, the molar ratio of the silicon-based core to the titanium nitride layer is 1:(0.02~0.08).
[0007] Furthermore, the molar ratio of the silicon-based core to the MOFs coating layer is 1:(0.01~0.05).
[0008] Furthermore, the material particle size of the silicon-based core is 1-8 μm; and / or the material particle size of the titanium nitride layer is 4-15 μm; and / or the material particle size of the MOFs coating layer is 20-150 μm.
[0009] According to another aspect of the present invention, a method for preparing the above-mentioned secondary battery of the present invention is provided, comprising the following steps: step S1, mixing a silicon source and a titanium source, and calcining them under a nitrogen atmosphere to obtain an in-situ composite material; step S2, adding the in-situ composite material to a solution of a MOFs ligand, performing a first stirring, and obtaining a first stirred solution; step S3, adding a solution of a MOFs metal salt to the first stirred solution, performing a second stirring, and obtaining a second stirred solution; step S4, drying the second stirred solution to obtain a silicon-based negative electrode material; step S5, using the silicon-based negative electrode material to prepare a negative electrode, and then assembling the positive electrode, the negative electrode, the electrolyte and the separator to obtain a secondary battery.
[0010] Further, in step S1, the silicon source includes one or more of silicon, silicon dioxide, silicon monoxide and nano-silicon; preferably, the silicon source includes silicon and silicon dioxide, and the molar ratio of the two is (2.0~2.2):2; and / or the titanium source includes titanium hydride and / or titanium dioxide; and / or the molar ratio of the silicon source to the titanium source is (4.0~4.2):(0.02~0.08); and / or the calcination temperature is 600~1100°C, and the time is 5~12h.
[0011] Further, in step S2, the MOFs ligand includes an organic carboxylic acid; preferably, the organic carboxylic acid includes one or more of 2-methylimidazole, triazole, oxalic acid, pyridinedicarboxylic acid, terephthalic acid, succinic acid and tris-benzoic acid; and / or the solvent of the solution of the MOFs ligand includes methanol; and / or the molar ratio of the in-situ composite material to the MOFs ligand is (40~60):10.
[0012] Further, in step S3, the MOFs metal salt includes one or more of cobalt salts, nickel salts, copper salts, iron salts and manganese salts; preferably, the cobalt salt includes one or more of cobalt nitrate hexahydrate, cobalt oxalate dihydrate, cobalt carbonate, cobalt chloride hexahydrate and cobalt sulfate heptahydrate; and / or the solvent of the MOFs metal salt solution includes methanol; and / or the molar ratio of MOFs ligand to MOFs metal salt is 10:(1~5).
[0013] Further, in step S1, the rotation speed of the first stirring is 100-200 rpm, and the time is 0.5-2 h; and / or the rotation speed of the second stirring is 50-100 rpm, and the time is 12-24 h.
[0014] Furthermore, in step S4, the drying temperature is 70-90°C and the drying time is 10-14 hours; and / or before drying, step S4 also includes the steps of centrifuging and washing the second stirred solution in sequence; preferably, methanol is used for washing.
[0015] The technical solution of the present invention is applied, and a composite silicon-based material is used in the negative electrode of the secondary battery, and a titanium nitride layer is coated on the surface of the silicon-based core. The titanium nitride has a stable structure and is resistant to high temperatures. The composite with the silicon-based core can significantly enhance the conductivity of semiconductor silicon. The MOFs material is coated on the surface of the titanium nitride layer. The MOFs material has a large specific surface area, a high porosity and a stable structure. Coating on the silicon-based core@titanium nitride surface can inhibit the volume expansion of silicon and significantly enhance its stability. At the same time, it avoids direct contact between the silicon-based material and the electrolyte, and the cycle performance is significantly improved. The silicon-based negative electrode material of the present invention has the advantages of high conductivity and long cycle, and can significantly enhance the conductivity, energy density and cycle performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0017] Figure 1 A schematic structural diagram of a silicon-based negative electrode material according to Example 1 of the present invention is shown;
[0018] Figure 2 A schematic structural diagram of a secondary battery according to an embodiment of the present invention is shown;
[0019] Figure 3 A schematic structural diagram of a battery cell assembly according to an embodiment of the present invention is shown.
[0020] The above drawings include the following reference numerals:
[0021] 1. Silicon-based core; 2. Titanium nitride layer; 3. MOFs coating layer; 10. Shell; 11. Receiving cavity; 20. Bare battery cell; 30. Thermal conductor; 40. Top cover assembly; 41. Pole; 5. Winding layer; 51. Negative electrode sheet; 52. Positive electrode sheet; 53. Isolation film; X, length direction; Z, thickness direction. DETAILED DESCRIPTION
[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0023] It should be noted that the “@” in the specification means that the latter material will coat the former material. For example, silicon oxide @ titanium nitride @ ZIF-8 means that titanium nitride is coated on the surface of silicon oxide, and ZIF-8 is coated on the surface of titanium nitride.
[0024] As described in the background of the present invention, in the prior art, when the negative electrode of a secondary battery uses a silicon-based material, its conductivity is low and its volume expands severely, resulting in poor conductivity and cycle performance of the battery. In order to solve the above problems, in a typical embodiment of the present invention, a secondary battery is provided, including a positive electrode, a negative electrode, a separator and an electrolyte, wherein the negative electrode includes a silicon-based negative electrode material, such as Figure 1 As shown, the silicon-based negative electrode material includes: a silicon-based core 1, a titanium nitride layer 2 coated on the surface of the silicon-based core, and a MOFs coating layer 3 coated on the surface of the titanium nitride layer; the material of the silicon-based core includes one or more of silicon monoxide, silicon dioxide, silicon and silicon-carbon materials; the material of the MOFs coating layer includes one or more of ZIF-8, ZIF-67 and UIO-66.
[0025] The SEI film on the surface of the silicon negative electrode ruptures as the volume of silicon expands, and the newly exposed silicon on the surface continues to consume lithium ions and electrolyte, causing irreversible capacity loss; at the same time, the residual SEI film continues to accumulate in thickness as the cycle proceeds, hindering the diffusion of lithium ions and electron transfer, causing an increase in the internal resistance of the battery, reducing the charge and discharge efficiency, and thus limiting the cycle performance of lithium-ion batteries composed of silicon negative electrodes.
[0026] Common titanium nitride is used in lithium-ion batteries, and titanium nitride is often used as a coating layer to encapsulate the active material. The present invention uses a composite silicon-based material in the negative electrode of the secondary battery, and coats the titanium nitride layer on the surface of the silicon-based core. The titanium nitride structure is stable and resistant to high temperatures. The composite with the silicon-based core can significantly enhance the conductivity of semiconductor silicon. The MOFs material is coated on the surface of the titanium nitride layer. The MOFs material has a large specific surface area, a high porosity and a stable structure. Coating on the silicon-based core @ titanium nitride surface can inhibit the volume expansion of silicon, significantly enhance its stability, and avoid direct contact between the silicon-based material and the electrolyte, and the cycle performance is significantly improved. The silicon-based negative electrode material of the present invention has the advantages of high conductivity and long cycle, and can significantly enhance the conductivity, energy density and cycle performance of the secondary battery.
[0027] Moreover, the above-mentioned silicon-based core can provide a higher specific capacity, and the above-mentioned MOFs coating layer material has a larger specific surface area, higher porosity, and more stable structure, which is conducive to further alleviating the volume expansion of silicon, constructing a ternary composite material, and increasing the conductivity and cycle performance of the material.
[0028] In order to better improve the first efficiency and cycle performance of the battery by controlling the content of titanium nitride, in a preferred embodiment, the molar ratio of the silicon-based core to the titanium nitride layer is 1:(0.02~0.08) to further improve the conductivity of the material.
[0029] For similar reasons, in a preferred embodiment, the molar ratio of the silicon-based core to the MOFs coating is 1:(0.01~0.05) to further inhibit the volume expansion of silicon and enhance its stability, and the cycle performance is more significantly improved.
[0030] In a preferred embodiment, the particle size of the silicon-based core material is 1-8 μm; and / or the particle size of the titanium nitride layer material is 4-15 μm; and / or the particle size of the MOFs coating layer material is 20-150 μm. Within the above particle size range, the material bonding and coating effects are better, and good composite further improves the compaction density and electrical properties of the material.
[0031] In another typical embodiment of the present invention, a method for preparing the above-mentioned secondary battery of the present invention is also provided, comprising the following steps: step S1, mixing a silicon source and a titanium source, and calcining them under a nitrogen atmosphere to obtain an in-situ composite material; step S2, adding the in-situ composite material to a solution of a MOFs ligand, performing a first stirring, and obtaining a first stirred solution; step S3, adding a solution of a MOFs metal salt to the first stirred solution, performing a second stirring, and obtaining a second stirred solution; step S4, drying the second stirred solution to obtain a silicon-based negative electrode material; step S5, using the silicon-based negative electrode material to prepare a negative electrode, and then assembling the positive electrode, the negative electrode, the electrolyte and the diaphragm to obtain a secondary battery.
[0032] Specifically, the present invention starts from the two aspects of conductivity and cycle performance. First, the silicon source and the titanium source are mixed, calcined in a nitrogen atmosphere, and an in-situ grown silicon-based core @ titanium nitride composite material is generated; titanium nitride has excellent conductivity and a stable chemical structure, and can enhance the conductivity and stability of the silicon negative electrode. Then the in-situ composite material is added to the solution of MOFs ligands and the solution of MOFs metal salts and then dried, and MOFs are coated on the surface of the silicon-based core @ titanium nitride composite material by chemical compounding to obtain a silicon-based negative electrode material, which curbs the volume expansion of the silicon negative electrode during the cycle and significantly enhances its cycle performance. Finally, the silicon-based negative electrode material is used to prepare the negative electrode, and the positive electrode, the negative electrode, the electrolyte and the diaphragm are assembled to obtain a secondary battery. The above preparation method is simple and easy to operate, and the prepared secondary battery has significantly improved conductivity and cycle performance.
[0033] In a preferred embodiment, in step S1, the silicon source includes one or more of silicon, silicon dioxide, silicon monoxide and nano-silicon; preferably, the silicon source includes silicon and silicon dioxide, and the molar ratio of the two is (2.0-2.2):2; and / or the titanium source includes titanium hydride and / or titanium dioxide; and / or the molar ratio of the silicon source to the titanium source is (4.0-4.2):(0.02-0.08); and / or the calcination temperature is 600-1100°C and the time is 5-12h. Under the above conditions, it is more conducive to the in-situ growth of titanium nitride on the surface of the silicon-based core, and the conductive properties and chemical structure advantages of titanium nitride are better utilized to further enhance the conductivity and cycle stability of the material.
[0034] In order to more fully coat MOFs on the surface of the silicon-based core@titanium nitride composite material through chemical compounding, the present application preferably defines the raw materials and addition amounts of MOFs as follows. In a preferred embodiment, in step S2, the MOFs ligand includes an organic carboxylic acid; preferably, the organic carboxylic acid includes one or more of 2-methylimidazole, triazole, oxalic acid, dipyridine carboxylic acid, terephthalic acid, succinic acid and tris-benzoic acid; and / or the solvent of the solution of the MOFs ligand includes methanol; and / or the molar ratio of the in-situ composite material to the MOFs ligand is (40~60):10.
[0035] Based on similar reasons, in a preferred embodiment, in step S3, the MOFs metal salt includes one or more of cobalt salts, nickel salts, copper salts, iron salts and manganese salts; preferably, the cobalt salt includes one or more of cobalt nitrate hexahydrate, cobalt oxalate dihydrate, cobalt carbonate, cobalt chloride hexahydrate and cobalt sulfate heptahydrate; and / or the solvent of the solution of the MOFs metal salt includes methanol; and / or the molar ratio of the MOFs ligand to the MOFs metal salt is 10:(1~5).
[0036] In order to make the solution more fully mixed, in a preferred embodiment, in step S1, the speed of the first stirring is 100-200 rpm, and the time is 0.5-2 h; and / or the speed of the second stirring is 50-100 rpm, and the time is 12-24 h.
[0037] In order to further improve the preparation efficiency, in a preferred embodiment, in step S4, the drying temperature is 70-90° C. and the drying time is 10-14 h.
[0038] In a preferred embodiment, in step S4, before drying, step S4 also includes the steps of centrifuging and washing the second stirred solution in sequence; preferably, washing with methanol can further reduce impurities in the material and reduce its impact on the electrochemical performance.
[0039] Typically but not limiting, the molar ratio of the silicon-based core to the titanium nitride layer is 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08 or a boundary value consisting of any two of them.
[0040] Typically but not limiting, the molar ratio of the silicon-based core to the MOFs coating is 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05 or a boundary value consisting of any two of them.
[0041] Typically but not limiting, in step S1, the calcination temperature is 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C or a boundary value composed of any two of them, and the calcination time is 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a boundary value composed of any two of them.
[0042] Typically but not limiting, in step S2, the molar ratio of the in-situ composite material to the MOFs ligand is 40:10, 45:10, 50:10, 55:10, 60:10 or a boundary value consisting of any two of them.
[0043] Typically but not limiting, in step S3, the molar ratio of the MOFs ligand to the MOFs metal salt is 10:1, 10:2, 10:3, 10:4, 10:5 or a boundary value consisting of any two of them.
[0044] The core structure of the secondary battery of the present invention includes a bare cell, and its structure mainly includes a positive electrode, a negative electrode, a diaphragm, an electrolyte, and may also include a tab. The secondary battery may also include a battery casing. The positive electrode is usually composed of a lithium compound, and the negative electrode includes the silicon-based negative electrode material of the present invention. The diaphragm is located between the positive and negative electrodes, and its function is to prevent the positive and negative electrodes from directly contacting each other and causing a short circuit, while allowing lithium ions to pass through. The electrolyte contains lithium salts and organic solvents, which can promote the movement of ions during the charge and discharge process of the battery. The tab is a metal conductor that connects the cell to the external circuit, usually made of copper or aluminum, and extends from the top of the pole piece.
[0045] Exemplarily, the manufacturing process of the secondary battery is as follows: First, the positive electrode active material is mixed with a binder, a conductive agent and a solvent to form a positive electrode slurry, which is applied to a metal foil current collector using a coating machine and dried to form a positive electrode sheet; the silicon-based negative electrode material of the present invention is mixed with a binder, a conductive agent and a solvent to form a negative electrode slurry, which is applied to a metal foil current collector using a coating machine and dried to form a negative electrode sheet. Next, the pole piece is compacted by a roller press, and then the pole piece is cut into the required size using a slitter. After the pole piece is prepared, the pole piece and the diaphragm are combined into a bare cell by a winding or lamination process. In the winding process, the positive and negative pole pieces and the diaphragm are stacked in a specific order, and then wound into a bare cell by a winding machine. Subsequently, the electrolyte is injected and the battery is sealed to form a complete battery cell. Finally, the battery is activated through steps such as formation and capacity division.
[0046] For example, the schematic diagram of the secondary battery structure is shown in Figure 2 The bare cell 20 is located in the housing 11 of the housing 10, a heat conductor 30 may be used on the surface, and a top cover assembly 40 having a pole 41 is provided on the top. Figure 3 The negative electrode sheet 51 , the positive electrode sheet 52 , and the separator 53 are wound in a specific direction to form a winding layer 5 .
[0047] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0048] Example 1
[0049] A secondary battery, the negative electrode includes silicon-based negative electrode material silicon oxide @ titanium nitride @ ZIF-8, the structural schematic diagram is shown in Figure 1 The particle size of the silicon-based core material is 1-8 μm, the particle size of the titanium nitride is 4-15 μm, the particle size of the MOFs coating material is 20-150 μm, and the molar ratio of the silicon-based core, the titanium nitride layer, and the MOFs coating layer is 1:0.05:0.03.
[0050] The preparation method comprises the following steps:
[0051] Step S1, weigh 2 mol of pure silicon (Si), 2 mol of silicon dioxide (SiO2) and 0.05 mol of titanium hydride (TiH2), mix them evenly, and then place them in a nitrogen atmosphere for calcination at a temperature of 800°C for 8 hours to prepare a silicon oxide (SiO)@titanium nitride (TiN) composite material, cool it to room temperature, and grind it for later use.
[0052] Step S2, take 0.05 mol of MOFs ligand (2-methylimidazole) and disperse it in methanol solution, stir for 1 hour to obtain MOFs ligand solution. Take 0.25 mol of the prepared silicon dioxide (SiO)@titanium nitride (TiN) composite material, add it to the MOFs ligand solution (the molar ratio of the in-situ composite material to the MOFs ligand is 50:10), continue to stir at 100 rpm for 1 hour to obtain the first stirred solution.
[0053] Step S3, 0.01 mol of MOFs metal salt (cobalt nitrate hexahydrate) was dispersed in a methanol solution and stirred for 1 hour to obtain a MOFs metal salt solution. The MOFs metal salt solution was added to the first stirred solution (the molar ratio of MOFs ligand to MOFs metal salt was 10:2), and stirred at 50 rpm for 16 hours.
[0054] Step S4, centrifuging the reaction product, washing it with anhydrous methanol for three times, and then drying it in a vacuum drying oven at 80° C. for 12 h, and obtaining silicon dioxide (SiO)@titanium nitride (TiN)@ZIF-8 powder after drying and grinding, which is retained for later use;
[0055] Step S5, mixing the silicon-based negative electrode material, the conductive agent Super P and the binder PVDF according to the mass ratio of 80:10:10, then evenly coating the slurry on the copper foil and drying to obtain the negative electrode, and then assembling the positive electrode (NCM811), the negative electrode, the electrolyte (LiPF6) and the diaphragm (PTFE) to obtain a secondary battery.
[0056] Example 2
[0057] The difference from Example 1 is that the negative electrode includes silicon-based negative electrode material silicon oxide @ titanium nitride @ ZIF-8, wherein the particle size of the silicon-based core material is 1-8 μm, the particle size of the titanium nitride is 4-15 μm, the particle size of the MOFs coating layer material is 20-150 μm, and the molar ratio of the silicon-based core, the titanium nitride layer, and the MOFs coating layer is 1:0.02:0.01.
[0058] Example 3
[0059] The difference from Example 1 is that the negative electrode includes silicon-based negative electrode material silicon oxide @ titanium nitride @ ZIF-8, wherein the particle size of the silicon-based core material is 1-8 μm, the particle size of the titanium nitride is 4-15 μm, the particle size of the MOFs coating layer material is 20-150 μm, and the molar ratio of the silicon-based core, the titanium nitride layer, and the MOFs coating layer is 1:0.08:0.05.
[0060] Example 4
[0061] The difference from Example 1 is that the negative electrode includes silicon-based negative electrode material silicon dioxide @ titanium nitride @ ZIF-67, wherein the particle size of the silicon-based core material is 1-8 μm, the particle size of the titanium nitride is 4-15 μm, the particle size of the MOFs coating layer material is 20-150 μm, and the molar ratio of the silicon-based core, the titanium nitride layer, and the MOFs coating layer is 1:0.05:0.03.
[0062] Example 5
[0063] The difference from Example 1 is that the negative electrode includes a silicon-based negative electrode material silicon @ titanium nitride @ UIO-66, wherein the silicon-based core material has a particle size of 1-8 μm, the titanium nitride has a particle size of 4-15 μm, the MOFs coating layer material has a particle size of 20-150 μm, and the molar ratio of the silicon-based core, the titanium nitride layer, and the MOFs coating layer is 1:0.05:0.03.
[0064] Example 6
[0065] The difference from Example 1 is that, in step S1, 2.2 mol of pure silicon (Si), 2 mol of silicon dioxide (SiO2) and 0.02 mol of titanium hydride (TiH2) are weighed, mixed evenly, and then calcined in a nitrogen atmosphere at a temperature of 600°C for 12 h to prepare a silicon oxide (SiO)@titanium nitride (TiN) composite material, which is then cooled to room temperature and ground for later use.
[0066] Example 7
[0067] The difference from Example 1 is that, in step S1, 2 mol of pure silicon (Si), 2 mol of silicon dioxide (SiO2) and 0.08 mol of titanium hydride (TiH2) are weighed, mixed evenly, and then calcined in a nitrogen atmosphere at a calcination temperature of 1100°C for 5 hours to prepare a silicon oxide (SiO)@titanium nitride (TiN) composite material, which is then cooled to room temperature and ground for later use.
[0068] Example 8
[0069] The difference from Example 1 is that, in step S2, 0.05 mol of MOFs ligand (2-methylimidazole) is dispersed in a methanol solution and stirred for 1 hour to obtain a MOFs ligand solution. 0.20 mol of the prepared silicon dioxide (SiO)@titanium nitride (TiN) composite material is added to the MOFs ligand solution (the molar ratio of the in-situ composite material to the MOFs ligand is 40:10), and stirring is continued at 200 rpm for 0.5 hour to obtain a first stirred solution.
[0070] Example 9
[0071] The difference from Example 1 is that, in step S2, 0.05 mol of MOFs ligand (2-methylimidazole) is dispersed in a methanol solution and stirred for 1 hour to obtain a MOFs ligand solution. 0.30 mol of the prepared silicon dioxide (SiO)@titanium nitride (TiN) composite material is added to the MOFs ligand solution (the molar ratio of the in-situ composite material to the MOFs ligand is 60:10), and stirring is continued at 100 rpm for 2 hours to obtain a first stirred solution.
[0072] Example 10
[0073] The difference from Example 1 is that, in step S3, 0.005 mol of MOFs metal salt (cobalt nitrate hexahydrate) is dispersed in a methanol solution and stirred for 1 hour to obtain a MOFs metal salt solution. The MOFs metal salt solution is added to the first stirred solution (the molar ratio of MOFs ligand to MOFs metal salt is 10:1), and stirred at 50 rpm for 24 hours.
[0074] Embodiment 11
[0075] The difference from Example 1 is that, in step S3, 0.025 mol of MOFs metal salt (cobalt nitrate hexahydrate) is dispersed in a methanol solution and stirred for 1 hour to obtain a MOFs metal salt solution. The MOFs metal salt solution is added to the first stirred solution (the molar ratio of MOFs ligand to MOFs metal salt is 10:5), and stirred at 10 rpm for 12 hours.
[0076] Example 12
[0077] The difference from Example 1 is that, in step S4, the reaction product is centrifuged and washed three times with anhydrous methanol, and then dried in a vacuum drying oven at 70° C. for 14 h. After drying and grinding, silicon dioxide (SiO)@titanium nitride (TiN)@ZIF-8 powder is obtained and retained for later use;
[0078] Embodiment 13
[0079] The difference from Example 1 is that, in step S4, the reaction product is centrifuged and washed three times with anhydrous methanol, and then dried in a vacuum drying oven at 90° C. for 10 h, and silicon dioxide (SiO)@titanium nitride (TiN)@ZIF-8 powder is obtained after drying and grinding, and is retained for later use;
[0080] Embodiment 14
[0081] The difference from Example 1 is that the preparation method comprises the following steps:
[0082] Step S1, weigh 4 mol of silicon dioxide and 0.05 mol of titanium dioxide, mix them evenly, and then place them in a nitrogen atmosphere for calcination at a temperature of 800° C. for 8 hours to prepare a silicon dioxide (SiO)@titanium nitride (TiN) composite material, and grind them for later use after cooling to room temperature.
[0083] Step S2, take 0.05 mol of MOFs ligand (triazole) and disperse it in methanol solution, stir for 1 hour to obtain MOFs ligand solution. Take 0.25 mol of the prepared silicon dioxide (SiO)@titanium nitride (TiN) composite material, add it to the MOFs ligand solution (the molar ratio of the in-situ composite material to the MOFs ligand is 50:10), continue to stir at 100 rpm for 1 hour to obtain the first stirred solution.
[0084] Step S3, 0.01 mol of MOFs metal salt (cobalt oxalate dihydrate) was dispersed in a methanol solution and stirred for 1 hour to obtain a MOFs metal salt solution. The MOFs metal salt solution was added to the first stirred solution (the molar ratio of MOFs ligand to MOFs metal salt was 10:2), and stirred at 50 rpm for 16 hours.
[0085] Step S4, centrifuging the reaction product, washing it three times with anhydrous methanol, and then drying it in a vacuum drying oven at 80° C. for 12 h, and then grinding it for later use;
[0086] Step S5, mixing the silicon-based negative electrode material, the conductive agent Super P and the binder PVDF according to the mass ratio of 80:10:10, then evenly coating the slurry on the copper foil and drying to obtain the negative electrode, and then assembling the positive electrode (NCM811), the negative electrode, the electrolyte (LiPF6) and the diaphragm (PTFE) to obtain a secondary battery.
[0087] Embodiment 15
[0088] The difference from Example 1 is that the preparation method comprises the following steps:
[0089] Step S1, weigh 4 mol of nano-silicon and 0.05 mol of titanium hydride (TiH2), mix them evenly, and then place them in a nitrogen atmosphere for calcination at a temperature of 800°C for 8 hours to prepare a silicon@titanium nitride (TiN) composite material, cool it to room temperature, and grind it for later use.
[0090] Step S2, take 0.05 mol of MOFs ligand (terephthalic acid) and disperse it in methanol solution, stir for 1 hour, and obtain MOFs ligand solution. Take 0.25 mol of the prepared silicon dioxide (SiO)@titanium nitride (TiN) composite material, add it to the MOFs ligand solution (the molar ratio of the in-situ composite material to the MOFs ligand is 50:10), continue to stir at 100 rpm for 1 hour, and obtain the first stirred solution.
[0091] Step S3, 0.01 mol of MOFs metal salt (nickel nitrate) was dispersed in a methanol solution and stirred for 1 hour to obtain a MOFs metal salt solution. The MOFs metal salt solution was added to the first stirred solution (the molar ratio of MOFs ligand to MOFs metal salt was 10:2), and stirred at 50 rpm for 16 hours.
[0092] Step S4, centrifuging the reaction product, washing it three times with anhydrous methanol, and then drying it in a vacuum drying oven at 80° C. for 12 h, and then grinding it for later use;
[0093] Step S5, mixing the silicon-based negative electrode material, the conductive agent Super P and the binder PVDF according to the mass ratio of 80:10:10, then evenly coating the slurry on the copper foil and drying to obtain the negative electrode, and then assembling the positive electrode (NCM811), the negative electrode, the electrolyte (LiPF6) and the diaphragm (PTFE) to obtain a secondary battery.
[0094] Comparative Example 1
[0095] The difference from Example 1 is that the negative electrode includes silicon-based negative electrode material silicon oxide@titanium nitride.
[0096] Comparative Example 2
[0097] The difference from Example 1 is that the negative electrode includes silicon-based negative electrode material silicon oxide @ ZIF-8.
[0098] Comparative Example 3
[0099] The difference from Example 1 is:
[0100] The negative electrode includes silicon-based negative electrode material silicon oxide@ZIF-8@titanium nitride.
[0101] The secondary batteries prepared in the above examples and comparative examples were subjected to performance tests, and the results are shown in Table 1.
[0102] Test method:
[0103] Resistance: The prepared negative electrode material was tested using a Yuanneng Technology BER2500 electrode resistor. The electrode was cut into a 3×4 cm rectangle, and then 5 points were selected on each electrode to test the resistivity at different points.
[0104] Capacity retention rate: Place the battery in a constant temperature box, discharge the battery to 1.0V at a current density of 1C, let it stand for 2 minutes, then charge it to 2.0V at a current density of 1C at a constant current and constant voltage. Repeat the above steps for 200 cycles to obtain the cycle retention rate.
[0105] First efficiency: The ratio of discharge capacity to charge capacity of a silicon-based lithium-ion battery in the first charge and discharge cycle.
[0106] Table 1
[0107]
[0108] As can be seen from the above, compared with the comparative example, each embodiment of the present invention uses a composite silicon-based material in the negative electrode of the secondary battery, and a titanium nitride layer is coated on the surface of the silicon-based core. The titanium nitride structure is stable and resistant to high temperatures. The composite with the silicon-based core can significantly enhance the conductivity of semiconductor silicon. The MOFs material is coated on the surface of the titanium nitride layer. The MOFs material has a large specific surface area, a high porosity and a stable structure. Coating on the silicon-based core @ titanium nitride surface can inhibit the volume expansion of silicon and significantly enhance its stability. At the same time, it avoids direct contact between the silicon-based material and the electrolyte, and the cycle performance is significantly improved. The silicon-based negative electrode material of the present invention has the advantages of high conductivity and long cycle, and can significantly enhance the conductivity, energy density and cycle performance of the secondary battery.
[0109] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the overall effect is better.
[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A secondary battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The negative electrode comprises a silicon-based negative electrode material, and the structure of the silicon-based negative electrode material is composed of the following: A silicon-based core, a titanium nitride layer coated on the surface of the silicon-based core, and a MOFs coating layer coated on the surface of the titanium nitride layer; the molar ratio of the silicon-based core to the titanium nitride layer is 1:(0.02-0.08); The material of the silicon-based core includes one or more of silicon monoxide, silicon dioxide, silicon and silicon-carbon materials; The material of the MOFs coating layer includes one or more of ZIF-8, ZIF-67 and UIO-66; The method for preparing the secondary battery comprises the following steps: Step S1, mixing a silicon source and a titanium source, and calcining them in a nitrogen atmosphere to obtain an in-situ composite material; Step S2, adding the in-situ composite material to a solution of MOFs ligands, and performing a first stirring to obtain a first stirred solution; Step S3, adding a solution of MOFs metal salt to the first stirred solution, performing a second stirring to obtain a second stirred solution; Step S4, drying the second stirred solution to obtain the silicon-based negative electrode material; Step S5, using the silicon-based negative electrode material to prepare a negative electrode, and then assembling a positive electrode, the negative electrode, an electrolyte and a separator to obtain the secondary battery.
2. The secondary battery according to claim 1, characterized in that: The molar ratio of the silicon-based core to the MOFs coating layer is 1:(0.01-0.05).
3. The secondary battery according to claim 1 or 2, characterized in that: The material particle size of the silicon-based core is 1-8 μm; and / or The material particle size of the titanium nitride layer is 4-15 μm; and / or The material particle size of the MOFs coating layer is 20~150μm.
4. The secondary battery according to claim 1 or 2, characterized in that: In the step S1, The silicon source comprises one or more of silicon, silicon dioxide, silicon monoxide and nano-silicon; and / or The silicon source comprises silicon and silicon dioxide, and the molar ratio of the two is (2.0-2.2):2; and / or The titanium source comprises titanium hydride and / or titanium dioxide; and / or The molar ratio of the silicon source to the titanium source is (4.0-4.2): (0.02-0.08); and / or The calcination temperature is 600-1100° C. and the calcination time is 5-12 hours.
5. The secondary battery according to claim 1 or 2, characterized in that: In the step S2, The MOFs ligand comprises an organic carboxylic acid, and the organic carboxylic acid comprises one or more of 2-methylimidazole, triazole, oxalic acid, dipyridine carboxylic acid, terephthalic acid, succinic acid and tris-benzoic acid; and / or The solvent of the solution of the MOFs ligands includes methanol; and / or The molar ratio of the in-situ composite material to the MOFs ligand is (40-60):
10.
6. The secondary battery according to claim 1 or 2, characterized in that: In the step S3, The MOFs metal salt includes one or more of cobalt salt, nickel salt, copper salt, iron salt and manganese salt, and the cobalt salt includes one or more of cobalt nitrate hexahydrate, cobalt oxalate dihydrate, cobalt carbonate, cobalt chloride hexahydrate and cobalt sulfate heptahydrate; and / or The solvent of the MOFs metal salt solution includes methanol; and / or The molar ratio of the MOFs ligand to the MOFs metal salt is 10:(1-5).
7. The secondary battery according to claim 1 or 2, characterized in that: In the step S1, The first stirring speed is 100-200 rpm, and the time is 0.5-2 h; and / or The second stirring has a rotation speed of 50-100 rpm and a time of 12-24 hours.
8. The secondary battery according to claim 1 or 2, characterized in that: In step S4, the drying temperature is 70-90° C. and the drying time is 10-14 hours; and / or Before the drying, the step S4 further comprises the steps of centrifuging and washing the second stirred solution in sequence, and methanol is used for the washing.